Detection of a high photoresponse at zero bias from a highly conducting ZnO:Ga based UV photodetector. Issue 104 (11th November 2015) - Sharma, Pankaj; Singh, Rohit; Awasthi, Vishnu; Pandey, Sushil K.; Garg, Vivek; Mukherjee, Shaibal
<x xml:space="preserve">Abstract</x> Ga-doped ZnO based ultraviolet photodetectors (PDs) were fabricated with a metal–semiconductor–metal structure. The room-temperature operable PDs had 58 mA W−1 responsivity at zero bias with internal and external quantum efficiency values of ∼22.5 and 37.4%.